Online oral examinations during Covid-19: A survey study at University College level - Graf, Stefan Ting; Rasmussen, Fie; Ruge, Dorthe (Tidsskriftet Læring og Medier (LOM), 2021)
During the Covid-19 pandemic, many teachers and students were forced to hold or take online oral examinations by video conferencing. Little research has been done on this topic either internationally or in Denmark. How do students experience examinations while sitting at home? How does the technology affect practice? How do students and teachers deal with nervousness? How is the exam dialogue experienced in a digital setting? In this study, we investigate the experiences of students and teachers with online oral examinations at a university college in Denmark. The study is based on the statistical analysis of a survey and a qualitative analysis of open text fields. Despite overall satisfaction with online oral examinations on the part of both students and examiners, the results indicate that there are conflicting experiences with online oral examinations.